Vertical distribution of methanotrophic archaea in an iron-rich groundwater discharge zone - Katsunori Yanagawa; Misaki Okabeppu; Sakiko Kikuchi; Fumito Shiraishi; Yumiko Nakajima; Akihiro Kano (PLoS ONE, 2025)
Anaerobic oxidation of methane coupled to iron reduction (Fe-AOM) is a crucial process for methane removal in terrestrial environments. However, the occurrence of Fe-AOM in natural environments is rare, and the mechanisms behind the direct coupling of methane oxidation and iron reduction remain poorly understood. In this study, we investigated the environmental factors influencing the distribution of methanotrophic archaea in an iron-rich zone of a freshwater pond in Hiroshima Prefecture, Japan. High concentration of dissolved ferrous iron supplied by groundwater discharge led to considerable ferrihydrite precipitation. Pore water methane increased with sediment depth, while nitrate and sulfate concentrations were near detection limits throughout the sediment column. The coexistence of ferric iron and methane suggests the ongoing process of Fe-AOM. Tracer-based experiments using 14C showed potential Fe-AOM rates up to 110 pmol mL-1 day-1. Throughout the sediment core, except at the surface, PCR-based molecular ecological analyses of the 16S rRNA gene and functional genes for anaerobic oxidation of methane revealed abundant sequences belonging to the family “Candidatus Methanoperedenaceae”. These geochemical and microbiological findings suggest that Fe-AOM plays a key role in biogeochemical cycles of iron and methane, positioning this environment as a modern analogue of early Earth conditions.